ADAMTS16 activates latent TGF-β, accentuating fibrosis and dysfunction of the pressure-overloaded heart. Issue 5 (11th July 2019) - Yao, Yufeng; Hu, Changqing; Song, Qixue; Li, Yong; Da, Xingwen; Yu, Yubin; Li, Hui; Clark, Ian M; Chen, Qiuyun; Wang, Qing K
Abstract: Aims: Cardiac fibrosis is a major cause of heart failure (HF), and mediated by the differentiation of cardiac fibroblasts into myofibroblasts. However, limited tools are available to block cardiac fibrosis. ADAMTS16 is a member of the ADAMTS superfamily of extracellular protease enzymes involved in extracellular matrix (ECM) degradation and remodelling. In this study, we aimed to establish ADAMTS16 as a key regulator of cardiac fibrosis. Methods and results: Western blot and qRT–PCR analyses demonstrated that ADAMTS16 was significantly up-regulated in mice with transverse aortic constriction (TAC) associated with left ventricular hypertrophy and HF, which was correlated with increased expression of Mmp2, Mmp9, Col1a1, and Col3a1 . Overexpression of ADAMTS16 accelerated the AngII-induced activation of cardiac fibroblasts into myofibroblasts. Protein structural analysis and co-immunoprecipitation revealed that ADAMTS16 interacted with the latency-associated peptide (LAP)-transforming growth factor (TGF)-β via a RRFR motif. Overexpression of ADAMTS16 induced the activation of TGF-β in cardiac fibroblasts; however, the effects were blocked by a mutation of the RRFR motif to IIFI, knockdown of Adamts16 expression, or a TGF-β-neutralizing antibody (ΝAb). The RRFR tetrapeptide, but not control IIFI peptide, blocked the interaction between ADAMTS16 and LAP-TGF-β, and accelerated the activation of TGF-β in cardiac fibroblasts. In TAC mice, the RRFR tetrapeptide aggravated cardiac fibrosis and hypertrophy by up-regulation of ECM proteins, activation of TGF-β, and increased SMAD2/SMAD3 signalling, however, the effects were blocked by TGF-β-NAb. Conclusion: ADAMTS16 promotes cardiac fibrosis, cardiac hypertrophy, and HF by facilitating cardiac fibroblasts activation via interacting with and activating LAP-TGF-β signalling. The RRFR motif of ADAMTS16 disrupts the interaction between ADAMTS16 and LAP-TGF-β, activates TGF-β, and aggravated cardiac fibrosis and hypertrophy. This study identifies a novel regulator of TGF-β signalling and cardiac fibrosis, and provides a new target for the development of therapeutic treatment of cardiac fibrosis and HF. Graphical Abstract: